The war that must not occur - Dupuy, Jean-Pierre (Stanford University Press, 2023)
"At a moment when humanity is on the precipice of nuclear catastrophe, philosopher Jean-Pierre Dupuy theorizes the limits of the logics of nuclear deterrence"--